The influence mechanism of ferrite grain size on strength stress at the fatigue of low-carbon steel - Vakulenko, I. A.; Proydak, S. V. (Science and Transport Progress, 2014)
Purpose. Explanation of the influence mechanism of ferrite grain size on the fatigue strength of low-carbon steel. Methodology. Material for research is the low-carbon steel with 0.1% of carbon contnent. The different size of ferrite grain was obtained due to varying the degree of cold plastic deformation and temperature of annealing. The estimation of grain size was conducted using methodologies of quantitative metallography. The microstructure of metal was investigated under a light microscope with increase up to 1500 times. As a fatigue response the fatigue strength of metal – a maximal value of load amplitude with endless endurance limit of specimen was used. Fatigue tests were carried out using the test machine «Saturn-10», at the symmetric cycle of alternating bend loading. Findings. On the basis of research the dependence for fatigue strength of low-carbon steel, which is based on an additive contribution from hardening of solid solution by the atoms of carbon, boundary of the ferrite grain and amount of mobile dislocations was obtained. It was established that as the grainy structure of low-carbon steel enlarges, the influence of grain size on the fatigue strength level is reduced. For the sizes of grains more than 100 mcm, basic influence on fatigue strength begins to pass to the solid solution hardening, which is determined by the state of solid solution of introduction. Originality. From the analysis of the obtained dependences it ensues that with the increase of ferrite grain size the required amount of mobile dislocations for maintenance of conditions for spreading plastic deformation becomes less dependent from the scheme of metal loading. Practical value. The obtained results present certain practical interest when developing of recommendations, directed on the increase of resource of products work from low-carbon steels in the conditions of cyclic loading. Estimation of separate contribution of the studied processes of structural changes with fatigue load allows one to choose a rational solution – to use the hardening effect from the ferrite alloying or to change the grain size of ferrite.